Associations between Systemic Sclerosis and Thyroid Diseases - Fallahi, Poupak; Ruffilli, Ilaria; Giuggioli, Dilia; Colaci, Michele; Ferrari, Silvia Martina; Antonelli, Alessandro; Ferri, Clodoveo (Frontiers in Endocrinology, 2017)
We have reviewed scientific literature about the association of systemic sclerosis (SSc) and thyroid disorders. Many studies demonstrated a high prevalence, and incidence, of new cases of hypothyroidism and autoimmune thyroiditis (AT) in sclerodermic patients, overall in female gender. It has been also demonstrated that hypovitaminosis D, and a Th1 predominance are associated with AT in systemic sclerosis (SSc) patients. A limited number of cases of Graves' disease (GD) have been also reported in SSc patients, in agreement with the higher prevalence of thyroid autoimmunity. Furthermore a higher prevalence of papillary thyroid cancer has been recently reported in SSc patients, particularly in the presence of AT. However studies in larger number of SSc patients are needed to confirm findings about GD and thyroid cancer (TC). During the follow-up of SSc patients it would be appropriate to monitor carefully their thyroid status. On the whole, data from the literature strongly suggest that female SSc patients, with a borderline high (although in the normal range) thyroid-stimulating hormone level, antithyroid peroxidase antibody positivity, and a hypoechoic pattern and small thyroid, should undergo periodic thyroid function follow-up, and appropriate treatments when needed. In conclusion most of studies show and association among SSc, AT and hypothyroidism; such as an increased prevalence of TC overall in SSc patients with AT. A limited number of cases of GD have been also reported in SSc.